Pengaruh Penggunaan Smartphone Terhadap Kedisiplinan Dan Kualitas Belajar Peserta Didik Kelas X-9 Di Sekolah SMA Negeri 13 Medan - Supriadi Cerdas Zalukhu; Evi Susilawati; Sapta Kesuma; Yusnita Muslim (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This research aims to explore the influence of smartphone use on the discipline and quality of learning of class X-9 students at SMA Negeri 13 Medan. Using a quantitative approach with survey methods, this research involved 36 students as samples. The research results show that smartphone use has a significant negative impact on student discipline and learning quality. The Pearson correlation test revealed a significant negative correlation between smartphone use and discipline (r = -0.45, p < 0.05) and learning quality (r = -0.50, p < 0.05). In addition, a simple regression test shows that smartphone use significantly influences student discipline and learning quality. The implications of this research emphasize the need for stricter supervision of smartphone use in schools as well as digital education that encourages wise use of technology. The results of this research can be a reference for schools and parents to minimize the negative impact of smartphone use and maximize its benefits in the learning process.